Biological nitrate removal using waste-derived extracts as sole carbon source. (1st January 2014) - Basu, Subhankar; Verma, Sakshi; Singh, Ravi Karan; Batra, Vidya S.; Balakrishnan, Malini
Waste-derived multicomponent extracts were investigated as carbon source for biological nitrate removal. Aerobic and anaerobic sludge from a municipal wastewater treatment plant and leachate from an anaerobic digester treating food waste were studied. Alkaline-heat treatment was used for sludge solubilisation. More than 90% carbon was recovered at pH 10–11. The extracts contain very high volatile fatty acids (VFAs), protein and carbohydrate. The protein/carbohydrate ratio was 2/1 for both aerobic and anaerobic sludge extracts and 9/1 for leachate. Of the total chemical oxygen demand (COD), 60% was solubilised in both the aerobic and anaerobic sludge extracts, while 80% was solubilised in the leachate. The extracts were successfully tested in batch experiments for different time intervals as a sole carbon source for biological nitrate removal in synthetic wastewater. More than 95% nitrate removal was achieved in 24 h batch studies at carbon-to-nitrate (C/N) ratio of 8 and at 35ºC. The nitrate removal performance was comparable to that obtained with glucose as the external carbon source. Further, the nitrate removal efficiency of all the three extracts is similar. Thus, the result of this study shows the potential of these waste derived materials for the low-cost treatment of nitrate rich wastewaters characterised by low C/N ratio that are generated from many industries.